2012
DOI: 10.1007/s11524-011-9656-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Suicide and Suicide Attempt in Subway Stations: A Population-based Ecological Study

Abstract: Suicidal behavior on the subway often involves young people and has a considerable impact on public life, but little is known about factors associated with suicides and suicide attempts in specific subway stations. Between 1979 and 2009, 185 suicides and 107 suicide attempts occurred on the subway in Vienna, Austria. Station-specific suicide and suicide attempt rates (defined as the frequency of suicidal incidents per time period) were modeled as the outcome variables in bivariate and multivariate Poisson regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 22 publications
(46 reference statements)
5
43
0
Order By: Relevance
“…In the multivariate model, station density was the factor with the strongest effect. This supports the finding in Vienna, where positive association between the number of station and railway suicide was reported (Niederkrotenthaler et al, 2012). The current findings also strengthen the evidence for the relationships of an elevated rate of railway suicide with higher train frequency and higher passenger volume (Too et al, 2014).…”
Section: Sex and Agesupporting
confidence: 91%
See 1 more Smart Citation
“…In the multivariate model, station density was the factor with the strongest effect. This supports the finding in Vienna, where positive association between the number of station and railway suicide was reported (Niederkrotenthaler et al, 2012). The current findings also strengthen the evidence for the relationships of an elevated rate of railway suicide with higher train frequency and higher passenger volume (Too et al, 2014).…”
Section: Sex and Agesupporting
confidence: 91%
“…The current findings also strengthen the evidence for the relationships of an elevated rate of railway suicide with higher train frequency and higher passenger volume (Too et al, 2014). However, contrary to the previous results (Niederkrotenthaler et al, 2012), our adjusted model showed that an increased number of video surveillance systems at stations and carparks was associated with a reduced risk of railway suicide.…”
Section: Sex and Agesupporting
confidence: 74%
“…Video surveillance and CCTV systems to facilitate the intervention of security staff at stations may increase the difficulties for suicide attempters to complete the act (Lindberg, 2012;Ratnayake et al, 2007). This is supported by Niederkrotenthaler et al (2012) who have shown that the presence of a surveillance unit at stations is associated with a decrease of suicidal behaviours (see Table 5 for details). In addition, the mere presence of human personnel at stations is believed to be a deterrent in itself: station staffing and the presence of human personnel at stations may discourage suicide (Clarke and Poyner, 1994), but also trespass (RSSB, 2005).…”
Section: Enforcement Punishment and Patrolsmentioning
confidence: 96%
“…Organisations or industries can identify the risk of suicide associated with particular groups or individuals: patients in services that are located near railways (Bhui et al, 2013), patients with affective and psychotic disorders (van Houwelingen and Kerkhof, 2008), drug users in subway stations (Niederkrotenthaler et al, 2012), or the causes of suicide in different age groups (Routley et al, 2004). Other risk assessment recommendations include the identification and monitoring of regional and local suicide hotspots (Brown et al, 2012;Debbaut et al, 2013;Erazo et al, 2004a) and station audits (RSSB, 2013).…”
Section: Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation